2020
DOI: 10.1136/bcr-2019-233397
|View full text |Cite
|
Sign up to set email alerts
|

Clinical conundrum: status epilepticus culminating into acute dystonia myoclonus

Abstract: A 7-year-old child who suffered from symptomatic focal epilepsy as a sequel to perinatal hypoxia used to have frequent seizures. This time she developed prolonged status epilepticus lasting for over 5 hours. She received a treatment in the form of intravenous midazolam and reinitiation of sodium valproate and clobazam that were discontinued previously. Seizures were controlled over a couple of hours, but she remained unresponsive. Later, she developed acute onset dystonia (day 3 post-status epilepticus) and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…29 It is also possible that imaging indicated the diagnosis, introducing a selection bias in cases of subacute sclerosing panencephalitis with movement disorders reported so far. Correlation with basal ganglia signal change has also been reported among children with subacute sclerosing panencephalitis with dystonia 11,12,15 and chorea-athetosis 20 (Supplementary Table S1). However, presence of radiologic abnormalities does not seem to correlate with worse prognosis or earlier disease progression in subacute sclerosing panencephalitis.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…29 It is also possible that imaging indicated the diagnosis, introducing a selection bias in cases of subacute sclerosing panencephalitis with movement disorders reported so far. Correlation with basal ganglia signal change has also been reported among children with subacute sclerosing panencephalitis with dystonia 11,12,15 and chorea-athetosis 20 (Supplementary Table S1). However, presence of radiologic abnormalities does not seem to correlate with worse prognosis or earlier disease progression in subacute sclerosing panencephalitis.…”
Section: Discussionmentioning
confidence: 64%
“…Movement disorders other than myoclonus, which are reported among a small proportion (1.6%-5.3%) of patients with subacute sclerosing panencephalitis, have been mainly described among adult patients with advanced disease. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] Moreover, these descriptions chiefly emanate from individual case reports and small case series, which have observed chorea-athetosis, dystonia, parkinsonism, tics, stereotypies, and tremors (Supplementary Table S1). Movement disorders offer an opportunity for symptomatic relief, and an avenue to offer improvement in quality of life among patients with subacute sclerosing panencephalitis, especially considering that therapeutic efforts largely unsuccessful.…”
Section: Introductionmentioning
confidence: 99%
“…Among 56 patients below 20 years presenting with dystonia at one center, 35 three had SSPE. One study reported a child with fulminant presentation, in association with periodic myoclonus 36 . Videos 2 and 3 show patients with SSPE with dystonia.…”
Section: Resultsmentioning
confidence: 99%
“…One study reported a child with fulminant presentation, in association with periodic myoclonus. 36 Videos 2 and 3 show patients with SSPE with dystonia.…”
Section: Dystoniamentioning
confidence: 99%